The power spectrum of the Lyman-α clouds - Amendola, Luca; Savaglio, Sandra (Arxiv, 1997)
We estimate the 1--D power spectrum and the integral density of neighbors in 14 QSO lines of sight. We discuss their variation with respect to redshift and column density and compare the results with standard CDM models.